Hybrid nanowire-hyperbolic metamaterial based broadband absorber for the visible and near-infrared regions. (December 2021) - Buranasiri, Prathan; Plaipichit, Suwan; Puttharugsa, Chokchai; Wicharn, Surawut
Abstract: In this work, spectral absorbance of hybrid nanowire-hyperbolic metamaterial was investigated numerically by using transfer-matrix method. The hybrid nanowire-hyperbolic metamaterial is consisted of two-dimensional periodically arranged arrays of subwavelength-sized hybrid nanowires (with circular cross-section) embedded in silicon dioxide host matrix. Each hybrid nanowire is made by core-shell structure used silicon as a core and gold as a shell. The hybrid nanowire-hyperbolic metamaterial is used as a top layer of a broadband absorber. The top layer is over on a planar silicon dioxide layer, which is backed by a nano-sized layer of gold as a perfect reflector for guaranteeing high absorbance. When electromagnetic waves in the range of 400–1600 nm wavelength are obliquely incident on the top hybrid nanowire-hyperbolic metamaterial surface, the absorption spectra of the designed absorber structure are analyzed for different incident angles, and radii of hybrid nanowire components or fill-factor of the hyperbolic metamaterial layer. The multiple absorption peaks, which are continuously generated from multiple longitudinal and transverse surface plasmon modes and are supported by the hybrid nanowires, are observed directly. The absorption feature can be also tuned by various operational conditions. The proposed structure is made by in-complex nano-fabricating techniques comparing with the another and it provides acceptable broadband absorptivity. Highlights: HNW-HMM based broadband absorber exhibits high absorbance in visible to NIR regions. HNW-HMM based broadband absorber is working in both TE- and TM-polarizations. HNW supports multiple longitudinal and transverse surface-plasmon resonant modes. HNW-HMM based broadband absorber can be made by uncomplicated nano-fabrications.